Legal Certainty Regarding the Regulation of Shipping Lanes as an Effort to Prevent Vessel Accidents - Yuliana Risna Maengkom; Hulman Panjaitan; Paltiada Saragi (UNIVERSITAS PAKUAN, 2026)
As an archipelagic state, Indonesia experiences high-intensity maritime traffic, which requires effective shipping lane management to ensure navigational safety and prevent ship accidents. The expansion of the fleet and increasing route density have elevated the risk of incidents, which in practice is often triggered by non-compliance with safety provisions (including rules for narrow channels) and weak supervision and law enforcement. This study aims to analyze (1) the constraints and challenges of current shipping lane management in Indonesia, and (2) the role of legal regulation in improving maritime safety and enforcing violations of shipping lanes in order to achieve legal certainty. The research employs a normative juridical method using statutory and analytical approaches, through a literature review of primary and secondary legal materials, including the ratified UNCLOS 1982 regime, national maritime/Shipping regulations, and technical provisions on navigational safety. The normative analysis indicates critical issues in the form of potential regulatory overlap and inter-agency coordination gaps, limited surveillance capacity, and suboptimal user compliance; these conditions imply that accident prevention has not been maximized and that legal certainty in maritime traffic governance remains weak. This study recommends regulatory harmonization, strengthening supervisory mechanisms and consistent enforcement of sanctions, as well as improving compliance standards for navigational safety as key prerequisites for sustainable ship-accident prevention.[1] Keywords: legal certainty; shipping lane management; maritime safety; law enforcement; ship accidents. [1] 1 For information on numbers for authors, the intention is to distinguish the origin of the institution (affiliation) of the authors, who sometimes collaborate with study programs or other agencies.